The impact of exports of copper and its concentrates from Peru to china: an analysis of the bilateral trade relationship during the years 2005 and 2018 - Napa Alva, Rosario Del Pilar (2023)
China's trade policy for Latin America represents one of the largest strategic plans to strengthen trade, economic and financial ties with the countries of this region. Different Latin American countries are positively observing the possibility of integrating commercially and economically with China through bilateral relations that include the signing of free trade agreements. This paper, of quantitative methodology with a longitudinal non-experimental approach, analyzes the impact that the signing of the Free Trade Agreement between Peru and China had on the exports of copper minerals and their concentrates, whose tariff heading is the most exported from Peru to China in the 2010s. Further. The results show that exports of copper minerals and their concentrates from Peru to China increased significantly after the signing of such an agreement, generating a positive impact on the economic development of Peru and on its trade expansion. These benefits are advantageous for the bilateral relationship, but above all for the economic improvement of Peru.